Reality check : Statens Museum for Kunst Copenhagen, 6 September 2008-4 January 2009 - Øckenholt, Marianne Torp.; Petersen, Anne Ring.; Koester, Joachim; Lund, Janna; Statens museum for kunst (Denmark) (Copenhagen : Statens Museum for Kunst, 2008)
Ader, Bas Jan ; Althamer, Pawel ; Zmijewski, Artur ; Auder, Michel ; Buckingham, Matthew ; Koester, Joachim ; Burden, Chris ; Deller, Jeremy ; Elmgreen, Michael & Dragset, Ingar ; Fischli, Peter & Weiss, David ; Floyer, Ceal ; Fudong, Yang ; Gaskell, Anna ; Gmelin, Felix ; Gonzalez-Torres, Felix ; Gordon, Douglas ; Graham, Rodney ; Grzeszykowska, Aneta ; Hammons, David ; von Hausswolff, Annika ; Hein, Jeppe ; Jakobsen, Henrik Plenge ; Jonas, Joan ; Leonard, Zoe ; Lislegaard, Ann ; Metinides, Enrique ; Nelson, Mike ; Olesen, Henrik & Hopf, Judith ; Philipsz, Susan ; Raad, Walid ; Sala, Anri ; Starling, Simon ; Tandberg, Vibeke ; Taylor-Wood, Sam ; Tomaselli, Fred ; Villesen, Gitte ; Vo, Danh
Editor, Sven Bjerkhof ; translation into English, Jeremy Watts.
kunstcatalogus
Keywords: Statens museum for kunst (Denmark) -- Exhibitions